Taqyīd al-Mubāḥ and Tobacco: Between Administrative and Legislative Authority - Shareef, Umar (Islamic law and society, 2023)
This article identifies the seventeenth-century Ottoman legal debate over the permissibility of tobacco as an early instance in which jurists such as Najm al-Dīn al-Ghazzī and Ibrāhīm al-Laqānī, and ʿAlāʾ al-Dīn al-Haṣkafī refer to the ‘ruler’s right to restrict the permissible’ (taqyīd al-mubāḥ) to justify sultan Murād iv’s restriction of smoking. In response, jurists such as ʿAbd al-Ghanī al-Nābulsī and ʿAlī b. Muḥammad al-Ajhūrī contested the application of taqyīd al-mubāḥ to tobacco on the grounds that it did not satisfy the required condition of securing public well-being (maṣlaḥa). My findings show that the jurists agreed on the administrative privilege of the ruler to restrict the permissible but disagreed over whether the ban against tobacco was based on maṣlaḥa or if an accidental property could temporarily prohibit the performance of a permissible act. This paper sheds light on the diversity of juristic positions with regard to the valid exercise of political power, the scope of the ruler’s legal jurisdiction, and the relationship between political and religious authorities.